(3eMGSHI GdHJQhd (B/s - (3GdbGVj, MSjfs; (3GdQjTGfj, SejQ s ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2010)
(3GdWHjYI GdLjhdhLjI hGdafjI hGdEbJUGOjI hGdEOGQjI dUfGYI GfJGL GdHJQhd(B- (3GdeYGjjQ GdeMGSHjI HTQcGJ GfJGL GdHJQhd(B- (3GMJjGWjGJ GdfaW hGdZGR(B- (3eMGSHI JcGdja GdESJcTGa(B- (3eMGSHI GdMUhd Ydi GdefGWb ZjQ GdeHQgfI(B- (3eMGSHI JcGdja GdMaQ hGdJWhjQ(B- (3eMGSHI JcGdja GdEfJGL(B- (3faGP JcGdja efGWb GdfaW hGdZGR GdeQSedI(B- (3eMGSHI GfNaGV bjeI GdefGWb ZjQ GdeHQgfI hGdeHQgfI(B- (3eMGSHI eHjYGJ GdefGWb GdeHQgfI hZjQ GdeHQgfI(B- (3eMGSHI YbhO JbGSe GdEfJGLs
(3cTGa eUWdMGJ U(B349(3; GdeQGLY U(B361s
Keywords: (3GdHJQhds; (3GdeMGSHI GdMchejIs; (3GfJGL GdfaWs